2013
DOI: 10.1107/s2052520613022129
|View full text |Cite
|
Sign up to set email alerts
|

Formation of isostructural solid solutions in 2,6-disubstitutedN-phenylformamides andN-phenylthioamides

Abstract: In order to investigate possible isostructural solid solutions of disubstituted N-phenylformamides and thioamides, we have studied the re-crystallization of pairs of compounds selected from 2,6-difluoro-N-phenylformamide (I), 2,6-dichloro-N-phenylformamide (II), 2,6-dimethyl-N-phenylformamide (III), 2,6-dichloro-N-phenylthioamide (IV), 2,6-dimethyl-N-phenylthioamide (V), 2,6-diisopropyl-N-phenylformamide (VI) and 2,6-diisopropyl-N-phenylthioamide (VII). For single-component 2,6-disubstituted-N-phenylformamides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…The formamide group and pyridine ring in (I) are somewhat twisted with a dihedral angle of 13.21 (5) . This is similar to N-phenyl-data reports formamide (Omondi et al, 2014) (dihedral angle between the benzene ring and formamide groups = 10.5 ) but in contrast to N-(2,6-difluorophenyl)formamide (Omondi et al, 2009b) and N-(2,6-dibromophenyl)formamide (Omondi et al, 2009a) where the equivalent dihedral angles are 58.4 and 83.2 , respectively. The latter structures indicate that the steric effects likely increase from H to F to Br; however, this large deviation from planarity is not observed in (I).…”
Section: Structure Descriptionsupporting
confidence: 87%
See 2 more Smart Citations
“…The formamide group and pyridine ring in (I) are somewhat twisted with a dihedral angle of 13.21 (5) . This is similar to N-phenyl-data reports formamide (Omondi et al, 2014) (dihedral angle between the benzene ring and formamide groups = 10.5 ) but in contrast to N-(2,6-difluorophenyl)formamide (Omondi et al, 2009b) and N-(2,6-dibromophenyl)formamide (Omondi et al, 2009a) where the equivalent dihedral angles are 58.4 and 83.2 , respectively. The latter structures indicate that the steric effects likely increase from H to F to Br; however, this large deviation from planarity is not observed in (I).…”
Section: Structure Descriptionsupporting
confidence: 87%
“…1). The amide bond lengths for (I) are 1.218 (3) A ˚and 1.366 (3) A ˚for the C O and C-N bonds, respectively, which are in good agreement with the corresponding bonds in the related compounds N-phenylformamide (Omondi et al, 2014), N-(2,6-difluorophenyl)formamide (Omondi et al, 2009b), and N-(2,6-dibromophenyl)formamide (Omondi et al, 2009a). As observed in other structures, the amide bond lengths for (I) are consistent with little to no N C/C-O bond resonance contribution.…”
Section: Structure Descriptionsupporting
confidence: 73%
See 1 more Smart Citation
“…Current understanding of principles governing the mixed crystallization of organic and inorganic compounds is based largely on work carried out decades ago by Kitaigorodsky and co-workers, which has not been subjected to extensive reexamination. , These pioneering studies suggested that a series of mixed crystals with continuously variable compositions in all proportions can only be obtained when the components are similar enough to crystallize isostructurally . However, more recent work has challenged this notion and shown that mixed crystals with a wide range of compositions can be formed from pairs that are not known to have a close crystallographic relationship. These recent advances, which include the discovery that mixed crystals can be effective seeds for inducing crystallization of the individual components, have made mixed crystallization an exciting area of research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as we have shown in our recent work−solid solutions may form when a similarly shaped molecule that does not disrupt the hydrogen bonding network in the crystal structure or can participate in this bonding equally well is introduced in the system. 10 Solid solutions have been discovered and studied for multicomponent systems of the following: enantiomers; 11−17 diastereomers; 13,18−21 molecules differing by single/double bonds between two carbon atoms; 22,23 molecules differing by halogen (and halogen/methyl) substituents; 24−28 molecules differing by S/O atoms; 29,30 molecules differing by F/H atoms; 31 aromatic systems differing by presence/absence of a heteroatom; 32−34 molecules differing by methyl/ethyl substituents. 35 Nevertheless, up to date, only somewhat rough and empirical guidelines could be established to define the criteria for solid solution formation, and there are cases when even very similar molecules do not mix in the solid state.…”
Section: ■ Introductionmentioning
confidence: 99%